The Effects of Export-Oriented, FDI-Friendly Policies on the Balance of Payments in a Developing Economy: A General Equilibrium Investigation - Arslan Razmi (University of Massachusetts, Department of Economics, 2005)
Many developing countries have adopted investor-friendly policies in recent years in order to attract export-oriented foreign direct investment (FDI). The effects of these policies on the external accounts have been largely ignored. This paper endogenizes FDI in°ows in a structuralist general equilibrium framework to contribute towards filling this gap. Our economy consists of: (i) a non-tradable goods sector and (ii) an export processing zone (EPZ) that hosts transnational corporations. The analysis finds that, contrary to widely-shared perceptions, the short-run effects of FDI-friendly policies on the balance of payments may frequently be negative due to the nature of both the investments and the policy measures. Moreover, balance of payments-related consequences of measures such as tax concessions and wage controls differ depending on: (i) which sector these are implemented in, (ii) the nature of international demand, and (iii) the extent of backward linkages between the EPZ and the domestic economy. JEL Categories: F21, F23, F41
Keywords: 330; Foreign direct investment; balance of payments; export processing zones; structuralist macroeconomics; real exchange rates; income redistribution; terms of trade; transnational corporations